Is the Hot Hand Present? Momentum, Stability & Performance - Simmons, Peter (2007)
This paper systematically reviews the determinants of momentum within the context of the English Premier League. The belief that past performance will determine future performance is tested within a human capital framework incorporating group dynamic effects. Results suggest i) The empirical evidence for the existence of the hot hand in the Premiership is limited; (ii) team quality is the most important predictor of team success; iii) age heterogeneity has a negative impact upon momentum whereas heterogeneity measured by career experience and quality has a positive effect; iii). In addition team stability facilitates shared experience which has a positive association with momentum generation; and iv) Home advantage will moderate the effect of the hot hand. This study provides important implications for the management of teams in organisational settings whilst identifying methodological flaws providing a leverage point for future research into causes and antecedents of momentum.